The psychosocial impact of career-ending injuries in elite rugby union players : a qualitative study - Hurley, Diarmuid (2014)
Retirement from sport can be a difficult transition for an athlete, particularly when participation in sport has formed a significant part of their identity and life as a whole. In the case of professional sport, athletes who retire because of a career-ending injury may have to deal with the unexpected double impact of losing their career and income and recovering from a serious injury, thus potentially making this exit from sport particularly problematic. This transition can be made all the more difficult since the athlete may be unprepared for it. Research on career-ending injuries among professional athletes, however, is limited. The purpose of this study was to document the lived experiences of former professional rugby union players who have suffered a career-ending sport injury. Three former professional Irish rugby union players took part in individual, semi-structured interviews. Following prolonged engagement and transcription, the data was analysed by following the guidelines for interpretative phenomenological analysis (Smith, Jarman & Osborn, 1999). Results indicated that, for the most part, the athletes perceived their career-ending injuries and subsequent transition out of rugby as a stressful, challenging and demanding process. The new post-injury reality faced by the athletes altered their perceptions of self, their psychological and physical wellbeing and their career and life plans. In particular, the severity of the injuries suffered by the athletes and the nature of the sport and organisation to which they were a part of, had a significant influence on their recovery and transition.Based on these findings, implications for athletes, sport organizations, sport medicine and allied health professionals working with injured athletes are presented.